Total Knee Arthroplasty after Correction of Tibial Diaphyseal Nonunion with Clamshell Osteotomy - Pingal Desai; Vivek Sharma; Karanvir Prakash (Case Reports in Orthopedics)
Total knee arthroplasty is mostly done to relieve pain and disability from a severe and degenerated knee. Deformities in the coronal and sagittal plane could be corrected with the help of cuts made in tibia and femur during total knee replacement as well as with ligament release. However, large deformities in the lower extremity particularly in the diaphysis region need correction prior to the total knee replacement. It helps to limit the amount of bone that will be cut and helps the ligament release. Several extra articular and intra-articular methods for the correction of diaphyseal deformity have been described. We present the case of clamshell osteotomy for the correction of diaphyseal deformity in the tibia and a total knee replacement after the osteotomy site healed.